Prevalence and Determinants of Sickness Absenteeism among Healthcare Workers in a Tertiary Hospital in Southwestern Nigeria (International Journal of Occupational Safety and Health, 2024)
Introduction: Sickness absenteeism is a global problem that affects almost all forms of workers, especially healthcare workers. This study assessed the prevalence and determinants of sickness absenteeism among healthcare workers in a tertiary hospital in Southwest, Nigeria.Methods: An institutional-based, cross-sectional study was conducted among 360 healthcare workers in a Tertiary Hospital in Southwest, Nigeria from October to December 2022. A pre-tested interviewer-administered, semi-structured questionnaire was used to elicit information from the respondents who were selected using a stratified sampling technique. Bivariate analysis and binary logistic regression analysis were performed to identify the predictors of sickness absenteeism using SPSS version 25.0. The significance of associations was determined at p-value